Antirust composite lubricating oil and preparation method thereof
By using the synergistic effect of MXene/PDA/MIL-53 composite material and composite anti-rust agent in lubricating oil, the problem of insufficient anti-rust and wear performance of existing lubricating oils is solved, and efficient protection and long-term metal parts are achieved Time to use.
Patent Information
- Application Number
- CN202411430840.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Existing lubricants have limited effects in improving rust and wear resistance, and it is difficult to meet the needs of equipment with high metal protection requirements.
MXene/PDA/MIL-53 composite material is used as antiwear agent, and the composite antirust agent is formed by blending heptadecane imidazoline perylene succinate and corrosion inhibitor, which can improve the prevention of lubricating oil by synergistically acting as a synergistic effect. Rust and wear resistance.
It significantly improves the anti-rust and wear performance of lubricating oil, so that it can effectively protect metal parts, extend service life, and is suitable for high-speed machinery and other equipment with high protection requirements.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, and in particular to an anti-rust composite lubricating oil and a preparation method thereof. Background Art
[0002] Rust-proof lubricating oil is a kind of lubricating oil that forms a protective film on the metal surface to prevent air and moisture from contacting it, thereby preventing metal parts from rusting. It can also lubricate metal moving parts, reduce wear and save energy. It is mainly composed of base oil and additives, and can be divided into two categories: mineral oil and synthetic oil. The base oil of mineral oil rust-proof oil is extracted from petroleum and has a lower cost, but its performance is not as good as synthetic oil, and its service life is relatively short. It is suitable for non-high-protection mechanical equipment and metal products. The base oil of synthetic oil rust-proof oil is synthesized through chemical changes, with more durable performance, better metal protection effect and longer service life. It is suitable for high-speed machinery, aircraft, ships and other equipment with high requirements for metal protection.
[0003] The anti-rust and anti-wear properties of lubricating oils are mainly improved by adding additives, but the effect is limited. Among them, rust inhibitors generally refer to sulfonates and ammonium salts, but the anti-rust effect of a single rust inhibitor is limited. The anti-rust performance can be improved by combining corrosion inhibitors and rust inhibitors and utilizing the synergistic effect between the two. The addition of anti-wear agents improves the anti-wear properties of lubricants, and nanomaterials as lubricating materials can improve the tribological properties of base oils. In various types of tribological applications, the shape of nanomaterials plays a vital role in their lubrication properties and mechanisms. Therefore, a composite lubricant with excellent anti-rust and anti-wear properties is developed. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an anti-rust composite lubricating oil and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An anti-rust composite lubricant, comprising the following raw materials in percentage by mass: 1%-5% anti-wear agent, 2%-6% composite anti-rust agent, 0.05%-3% antioxidant, and the balance being base oil; The anti-wear agent is a MXene / PDA / MIL-53 composite material; The base oil is one or more of mineral base oil, synthetic base oil and vegetable oil; The composite rust inhibitor is a mixture of heptadecenyl imidazoline alkenyl succinate and a corrosion inhibitor in a mass ratio of 1:0.5-1.5; Furthermore, the corrosion inhibitor is prepared by the following steps: Step A1, adding β-alanine and benzotriazole to type A insulating oil, and reacting at 130-160° C. for 6-8 hours, standing to separate layers, and collecting the lower layer product to obtain an intermediate; Step A2, dispersing the intermediate and sodium hydroxide in acetonitrile, recorded as solution 1; dispersing 4,4,5,5,5-pentafluoropentanol and sodium hydroxide in acetonitrile, recorded as solution 2; mixing cyanuric chloride and acetonitrile in an ice-water bath, slowly adding 1 / 2 volume of mixed solution 1, and reacting at 0° C. for 2-4 hours, then slowly adding the remaining volume of mixed solution 1, and reacting at 45-55° C. for 3-5 hours, then heating to 90° C., slowly adding mixed solution 2, continuing the reaction for 8-10 hours, filtering, washing, and drying to obtain a corrosion inhibitor; Furthermore, in step A1, the dosage ratio of β-alanine, benzotriazole and type A insulating oil is 0.05-0.15 mol: 0.06-0.18 mol: 200 mL; Furthermore, in step A2, the dosage ratio of cyanuric chloride, acetonitrile, mixed solution 1 and mixed solution 2 is 0.01-0.03 mol: 100 mL: 100 mL: 50 mL; Furthermore, in step A2, the usage ratio of the intermediate, sodium hydroxide and acetonitrile in the mixed solution 1 is 0.02-0.06 mol: 1-3 g: 100 mL, and the usage ratio of 4,4,5,5,5-pentafluoropentanol, sodium hydroxide and acetonitrile in the mixed solution 2 is 0.01-0.03 mol: 0.5-1.5 g: 50 mL.
[0006] The MXene / PDA / MIL-53 composite material is prepared by the following steps: Step B1, mix LiF and 9 mol / L hydrochloric acid solution evenly, then add Ti3AlC2 powder, heat to 35°C and stir to react for 12-24 hours, centrifuge and wash until the pH of the supernatant is 6.5-7, collect the precipitate, and redisperse it in deionized water, ultrasonicate for 1-3 hours, centrifuge and freeze-dry to obtain MXene nanosheets; Step B2, ultrasonically disperse the MXene nanosheets in a Tris-HCl buffer with a pH of 8.5 for 30 minutes, add dopamine hydrochloride, and stir at room temperature for 10-20 hours, centrifuge, wash, and dry to obtain MXene / PDA powder; Step B3, dispersing 2-aminoterephthalic acid in DMF, recorded as a mixed solution; ultrasonically dispersing MXene / PDA powder in deionized water, adding aluminum chloride hexahydrate and stirring for 30 minutes, then adding the mixed solution and stirring for 30 minutes, then transferring to a reactor, and reacting at 130-150°C for 10-24 hours, centrifuging, washing, and drying to obtain a MXene / PDA / MIL-53 composite material; Further, in step B1, the dosage ratio of Ti3AlC2 powder, LiF, hydrochloric acid solution and deionized water is 1-3 g: 1-2 g: 40-80 mL: 10 mL; Further, in step B2, the ratio of MXene nanosheets, Tris-HCl buffer and dopamine hydrochloride is 1-3 g: 200 mL: 0.5-2 g; Furthermore, in step B3, the dosage ratio of MXene / PDA powder, deionized water, aluminum chloride hexahydrate and the mixed solution is 0.5-2 g: 20 mL: 0.72-2.16 g: 80 mL, and the dosage ratio of 2-aminoterephthalic acid and DMF in the mixed solution is 0.54-1.62 g: 80 mL.
[0007] A method for preparing a rust-proof composite lubricating oil comprises the following steps: The raw materials are weighed according to the mass percentage, the base oil is heated to 60-80°C, and then the anti-wear agent, the composite rust inhibitor and the antioxidant are added while stirring to obtain the composite lubricating oil.
[0008] Beneficial effects of the present invention: The composite lubricant prepared by the present invention uses base oil as the main raw material, and adds various additives to further improve the overall performance of the lubricant; wherein the composite rust inhibitor utilizes the synergistic effect between the rust inhibitor and the corrosion inhibitor to improve the rust resistance of the lubricant; the MXene / PDA / MIL-53 composite material is used as an anti-wear agent, and the synergistic effect between nanomaterials is utilized to improve the anti-wear performance of the lubricant.
[0009] The composite rust inhibitor is obtained by blending heptadecenyl imidazoline alkenyl succinate and a corrosion inhibitor, and the synergistic effect between the two is utilized to improve the rust prevention performance of the lubricant; in the corrosion inhibitor, the carboxyl group in beta-alanine and the secondary amine in benzotriazole are first reacted to synthesize an intermediate, and then the intermediate is reacted with the amino group and the hydroxyl group in 4,4,5,5,5-pentafluoropentanol with cyanuric chloride; the benzotriazole and triazine structures in the corrosion inhibitor can act synergistically to coordinate with the metal surface atoms to form covalent bonds, prevent the metal from reacting with the corrosive medium, inhibit metal corrosion, and effectively improve the rust prevention performance of the lubricant; in addition, the introduction of hydrophobic fluorine atoms can reduce the surface energy of the metal surface, form a hydrophobic layer, further protect the metal matrix, play a corrosion inhibition role, and thus improve the rust prevention performance.
[0010] In the MXene / PDA / MIL-53 composite material, Ti3AlC2 powder is first etched with hydrochloric acid and LiF to obtain MXene nanosheets with a few-layer structure; then, a polydopamine film is formed on the surface of the MXene nanosheets by the self-polymerization of dopamine to obtain MXene / PDA powder; finally, MIL-53 is synthesized on the surface of MXene / PDA using aluminum chloride hexahydrate and 2-aminoterephthalic acid as raw materials to obtain a MXene / PDA / MIL-53 composite material. As a lubricant additive, MXene / PDA / MIL-53 composite material has stable dispersibility in base oil and improves the friction reduction and wear resistance of lubricant. This is due to the synergistic effect of MXene / PDA nanomaterials and MIL-53 during the friction process. Among them, MXene nanosheets are small in size and can easily enter the friction surface and reduce friction loss through interlayer sliding. At the same time, MIL-53 material with good flexibility and deformation ability grows on the surface of MXene nanosheets, which weakens the agglomeration of nanocomposites in the base oil. During the friction process, MIL-53 falls off and deposits on the wear surface to fill surface defects, thereby reducing friction and wear. In addition, the nanocomposite material may also undergo complex friction chemical reactions during the friction process to form a friction protection film, further improving the wear resistance. DETAILED DESCRIPTION
[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0012] The corrosion inhibitor is prepared by the following steps: Step A1, add 0.05 mol β-alanine and 0.06 mol benzotriazole into 200 mL type A insulating oil, and react at 130° C. for 6 h, stand to separate layers, and collect the lower layer product to obtain an intermediate; Step A2, 0.02 mol of the intermediate and 1 g of sodium hydroxide are dispersed in 100 mL of acetonitrile, recorded as solution 1; 0.01 mol of 4,4,5,5,5-pentafluoropentanol and 0.5 g of sodium hydroxide are dispersed in 50 mL of acetonitrile, recorded as solution 2; 0.01 mol of cyanuric chloride and 100 mL of acetonitrile are mixed evenly in an ice-water bath, 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 0° C. for 2 h, and then 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 45° C. for 3 h, and then the mixture is heated to 90° C., 50 mL of mixed solution 2 is slowly added, the reaction is continued for 8 h, and the mixture is filtered, washed, and dried to obtain a corrosion inhibitor.
[0013] The MXene / PDA / MIL-53 composites were prepared by the following steps: Step B1, 1g LiF and 40mL 9mol / L hydrochloric acid solution were mixed evenly, and then 1g Ti3AlC2 powder was added, and the temperature was raised to 35°C and stirred for 12h, centrifuged and washed until the pH of the supernatant was 6.5, the precipitate was collected, and redispersed in 10mL deionized water, ultrasonicated for 1h, centrifuged, and freeze-dried to obtain MXene nanosheets; Step B2, ultrasonically disperse 1 g of MXene nanosheets in 200 mL of Tris-HCl buffer with a pH of 8.5 for 30 min, add 0.5 g of dopamine hydrochloride, and stir at room temperature for 10 h, centrifuge, wash, and dry to obtain MXene / PDA powder; Step B3, disperse 0.54g of 2-aminoterephthalic acid in 80mL of DMF, record it as a mixed solution; ultrasonically disperse 0.5g of MXene / PDA powder in 20mL of deionized water, add 0.72g of aluminum chloride hexahydrate and stir for 30min, then add 80mL of the mixed solution and stir for 30min, then transfer to a reactor and react at 130°C for 10h, centrifuge, wash and dry to obtain a MXene / PDA / MIL-53 composite material. Example
[0014] The corrosion inhibitor is prepared by the following steps: Step A1, add 0.1 mol β-alanine and 0.12 mol benzotriazole into 200 mL type A insulating oil, and react at 140° C. for 7 h, stand to separate layers, and collect the lower layer product to obtain an intermediate; Step A2, 0.04 mol of the intermediate and 2 g of sodium hydroxide are dispersed in 100 mL of acetonitrile, recorded as solution 1; 0.02 mol of 4,4,5,5,5-pentafluoropentanol and 1 g of sodium hydroxide are dispersed in 50 mL of acetonitrile, recorded as solution 2; 0.02 mol of cyanuric chloride and 100 mL of acetonitrile are mixed evenly in an ice-water bath, 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 0° C. for 3 h, and then 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 50° C. for 4 h, and then the temperature is raised to 90° C., 50 mL of mixed solution 2 is slowly added, the reaction is continued for 9 h, and the mixture is filtered, washed, and dried to obtain a corrosion inhibitor.
[0015] The MXene / PDA / MIL-53 composites were prepared by the following steps: Step B1, 1.5g LiF and 60mL 9mol / L hydrochloric acid solution were mixed evenly, and then 2g Ti3AlC2 powder was added, and the temperature was raised to 35°C and stirred for 18h, centrifuged and washed until the pH of the supernatant was 6.7, the precipitate was collected, and redispersed in 10mL deionized water, ultrasonicated for 2h, centrifuged, and freeze-dried to obtain MXene nanosheets; Step B2, ultrasonically disperse 2 g of MXene nanosheets in 200 mL of Tris-HCl buffer with a pH of 8.5 for 30 min, add 1 g of dopamine hydrochloride, and stir at room temperature for 15 h, centrifuge, wash, and dry to obtain MXene / PDA powder; Step B3, disperse 1.1 g of 2-aminoterephthalic acid in 80 mL of DMF and record it as a mixed solution; ultrasonically disperse 1 g of MXene / PDA powder in 20 mL of deionized water, add 1.44 g of aluminum chloride hexahydrate and stir for 30 min, then add 80 mL of the mixed solution and stir for 30 min, then transfer to a reactor and react at 40 ° C for 16 h, centrifuge, wash and dry to obtain a MXene / PDA / MIL-53 composite material. Example
[0016] The corrosion inhibitor is prepared by the following steps: Step A1, add 0.15 mol β-alanine and 0.18 mol benzotriazole into 200 mL type A insulating oil, and react at 160° C. for 8 h, stand to separate layers, and collect the lower layer product to obtain an intermediate; Step A2, 0.06 mol of the intermediate and 3 g of sodium hydroxide are dispersed in 100 mL of acetonitrile, recorded as solution 1; 0.03 mol of 4,4,5,5,5-pentafluoropentanol and 1.5 g of sodium hydroxide are dispersed in 50 mL of acetonitrile, recorded as solution 2; 0.03 mol of cyanuric chloride and 100 mL of acetonitrile are mixed evenly in an ice-water bath, 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 0° C. for 4 h, and then 50 mL of mixed solution 1 is slowly added, and the mixture is reacted at 55° C. for 5 h, and then the temperature is raised to 90° C., 50 mL of mixed solution 2 is slowly added, the reaction is continued for 10 h, and the mixture is filtered, washed, and dried to obtain a corrosion inhibitor.
[0017] The MXene / PDA / MIL-53 composites were prepared by the following steps: Step B1, 2g LiF and 80mL 9mol / L hydrochloric acid solution were mixed evenly, and then 3g Ti3AlC2 powder was added, and the temperature was raised to 35°C and stirred for reaction for 24h, centrifuged and washed until the pH of the supernatant was 7, the precipitate was collected, and redispersed in 10mL deionized water, ultrasonicated for 3h, centrifuged, and freeze-dried to obtain MXene nanosheets; Step B2, ultrasonically disperse 3 g of MXene nanosheets in 200 mL of Tris-HCl buffer with a pH of 8.5 for 30 min, add 2 g of dopamine hydrochloride, and stir at room temperature for 20 h, centrifuge, wash, and dry to obtain MXene / PDA powder; Step B3, disperse 1.62g of 2-aminoterephthalic acid in 80mL of DMF, record it as a mixed solution; ultrasonically disperse 2g of MXene / PDA powder in 20mL of deionized water, add 2.16g of aluminum chloride hexahydrate and stir for 30min, then add 80mL of the mixed solution and stir for 30min, then transfer to a reactor and react at 150°C for 24h, centrifuge, wash and dry to obtain a MXene / PDA / MIL-53 composite material. Example
[0018] A method for preparing a rust-proof composite lubricating oil comprises the following steps: 1% MXene / PDA / MIL-53 composite material prepared in Example 1, 2% composite rust inhibitor, 0.05% antioxidant 703, and the balance is mineral base oil; The composite rust inhibitor is a mixture of heptadecenyl imidazoline alkenyl succinate and the corrosion inhibitor prepared in Example 1 in a mass ratio of 1:0.5; The raw materials were weighed according to mass percentage, the mineral base oil was heated to 60° C., and the MXene / PDA / MIL-53 composite material prepared in Example 1, the composite rust inhibitor, and the antioxidant 703 were added while stirring to obtain a composite lubricating oil. Example
[0019] A method for preparing a rust-proof composite lubricating oil comprises the following steps: 3% MXene / PDA / MIL-53 composite material prepared in Example 2, 4% composite rust inhibitor, 1% antioxidant 703, and the balance is mineral base oil; The composite rust inhibitor is a mixture of heptadecenyl imidazoline alkenyl succinate and the corrosion inhibitor prepared in Example 2 in a mass ratio of 1:1; The raw materials were weighed according to mass percentage, the mineral base oil was heated to 70° C., and the MXene / PDA / MIL-53 composite material prepared in Example 2, the composite rust inhibitor, and the antioxidant 703 were added while stirring to obtain a composite lubricating oil. Example
[0020] A method for preparing a rust-proof composite lubricating oil comprises the following steps: 5% MXene / PDA / MIL-53 composite material prepared in Example 3, 6% composite rust inhibitor, 3% antioxidant 703, and the balance is mineral base oil; The composite rust inhibitor is a mixture of heptadecenyl imidazoline alkenyl succinate and the corrosion inhibitor prepared in Example 3 in a mass ratio of 1:1.5; The raw materials were weighed according to mass percentage, the mineral base oil was heated to 80° C., and the MXene / PDA / MIL-53 composite material prepared in Example 3, the composite rust inhibitor, and the antioxidant 703 were added while stirring to obtain a composite lubricating oil.
[0021] Comparative Example 1 This comparative example is a composite lubricant, which differs from Example 6 in that the anti-wear agent SR5088 is used instead of the MXene / PDA / MIL-53 composite material prepared in Example 3, and the rest is the same.
[0022] Comparative Example 2 This comparative example is a composite lubricating oil, which is different from Example 6 in that only heptadecenyl imidazoline alkenyl succinate is used as the composite rust inhibitor, and the rest are the same.
[0023] The performance tests were performed on the samples prepared in Examples 4-6 and Comparative Examples 1-2: Anti-rust performance test: Liquid phase corrosion test was carried out according to GB / T11143 (B method), the test conditions were: artificial seawater, time was 24h, water bath temperature was 60℃; Anti-wear performance test: The anti-wear performance of lubricating oil was measured according to the SH / T0189 method. The test conditions were: oil temperature 75°C, load 392N, 1200r / min, and running time 60min. The test results are shown in the following table: Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Corrosion results Rust-free Rust-free Rust-free Rust-free Medium rust Wear spot diameter / mm 0.32 0.30 0.27 0.52 0.43 It can be seen from the above table that the composite lubricating oil prepared by the present invention is rust-free after the anti-rust performance test, indicating that the composite lubricating oil has excellent anti-rust performance; after the anti-wear performance test, the wear spot diameter is in the range of 0.27mm-0.32mm, indicating that it has excellent anti-wear performance.
[0024] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they shall all fall within the protection scope of the present invention.
Claims
1. A rust-proof composite lubricating oil, characterized in that: The raw materials include the following percentages by mass: 1%-5% anti-wear agent, 2%-6% composite rust inhibitor, 0.05%-3% antioxidant, and the balance is base oil; The anti-wear agent is a MXene / PDA / MIL-53 composite material; The composite rust inhibitor is a mixture of heptadecenyl imidazoline alkenyl succinate and a corrosion inhibitor in a mass ratio of 1:0.5-1.5; The corrosion inhibitor is prepared by the following steps: Step A1, adding β-alanine and benzotriazole to type A insulating oil, and reacting at 130-160° C. for 6-8 hours, standing to separate layers, and collecting the lower layer product to obtain an intermediate; Step A2, dispersing the intermediate and sodium hydroxide in acetonitrile, recorded as solution 1; dispersing 4,4,5,5,5-pentafluoropentanol and sodium hydroxide in acetonitrile, recorded as solution 2; mixing cyanuric chloride and acetonitrile in an ice-water bath, slowly adding 1 / 2 volume of mixed solution 1, and reacting at 0° C. for 2-4 hours, then slowly adding the remaining volume of mixed solution 1, and reacting at 45-55° C. for 3-5 hours, then heating to 90° C., slowly adding mixed solution 2, continuing the reaction for 8-10 hours, filtering, washing, and drying to obtain a corrosion inhibitor.
2. The rust-proof composite lubricating oil according to claim 1, characterized in that: In step A1, the dosage ratio of β-alanine, benzotriazole and type A insulating oil is 0.05-0.15 mol: 0.06-0.18 mol: 200 mL.
3. The rust-proof composite lubricating oil according to claim 1, characterized in that: In step A2, the usage ratio of cyanuric chloride, acetonitrile, mixed solution 1 and mixed solution 2 is 0.01-0.03 mol:100 mL:100 mL:50 mL.
4. The rust-proof composite lubricating oil according to claim 1, characterized in that: In step A2, the usage ratio of the intermediate, sodium hydroxide and acetonitrile in the mixed solution 1 is 0.02-0.06 mol: 1-3 g: 100 mL, and the usage ratio of 4,4,5,5,5-pentafluoropentanol, sodium hydroxide and acetonitrile in the mixed solution 2 is 0.01-0.03 mol: 0.5-1.5 g: 50 mL.
5. The rust-proof composite lubricating oil according to claim 1, characterized in that: The base oil is one or more of mineral base oil, synthetic base oil and vegetable oil.
6. The rust-proof composite lubricating oil according to claim 1, characterized in that: The MXene / PDA / MIL-53 composite material is prepared by the following steps: Step B1, mix LiF and 9 mol / L hydrochloric acid solution evenly, then add Ti3AlC2 powder, heat to 35°C and stir to react for 12-24 hours, centrifuge and wash until the pH of the supernatant is 6.5-7, collect the precipitate, and redisperse it in deionized water, ultrasonicate for 1-3 hours, centrifuge and freeze-dry to obtain MXene nanosheets; Step B2, ultrasonically disperse the MXene nanosheets in a Tris-HCl buffer with a pH of 8.5 for 30 minutes, add dopamine hydrochloride, and stir at room temperature for 10-20 hours, centrifuge, wash, and dry to obtain MXene / PDA powder; Step B3, disperse 2-aminoterephthalic acid in DMF, record it as a mixed solution; ultrasonically disperse MXene / PDA powder in deionized water, add aluminum chloride hexahydrate and stir for 30 minutes, then add the mixed solution and stir for 30 minutes, then transfer it to a reactor, and react at 130-150°C for 10-24 hours, centrifuge, wash and dry to obtain a MXene / PDA / MIL-53 composite material.
7. The rust-proof composite lubricating oil according to claim 6, characterized in that: In step B1, the dosage ratio of Ti3AlC2 powder, LiF, hydrochloric acid solution and deionized water is 1-3g:1-2g:40-80mL:10mL.
8. The rust-proof composite lubricating oil according to claim 6, characterized in that: In step B2, the dosage ratio of MXene nanosheets, Tris-HCl buffer and dopamine hydrochloride is 1-3 g: 200 mL: 0.5-2 g.
9. The rust-proof composite lubricating oil according to claim 6, characterized in that: In step B3, the dosage ratio of MXene / PDA powder, deionized water, aluminum chloride hexahydrate and the mixed solution is 0.5-2 g: 20 mL: 0.72-2.16 g: 80 mL, and the dosage ratio of 2-aminoterephthalic acid and DMF in the mixed solution is 0.54-1.62 g: 80 mL.
10. A method for preparing the rust-proof composite lubricating oil according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed according to the mass percentage, the base oil is heated to 60-80°C, and then the anti-wear agent, the composite rust inhibitor and the antioxidant are added while stirring to obtain the composite lubricating oil.
Citation Information
Patent Citations
Corrosion inhibitor composition and preparation method and application thereof
CN108842154A
Anti-rust bearing lubricating oil preparation method
CN109722326A
ZIF-8 / MXene PDA composite lubricating material and preparation method thereof
CN116804159A
High and low temperature resistant anhydrous engine coolant and preparation method thereof
CN117757444A
Ternary nanocomposite flame retardant, flame retardant epoxy resin and method for preparing the same
GB2622099A